Investigation of electrical and aging properties of Bi-modified (Zn0.4Ni0.6)1-xNaxO ceramic thermistors. Issue 7 (July 2021) - Gao, Caiyun; Li, Zhicheng; Yang, Lin; Peng, Dicheng; Zhang, Hong
Highlights: The resistivities and B values of the ceramics can be adjusted by doping Na-ion. The addition of Bi2 O3 enhances the sintering-ability. Composite with Bi2 O3 is an effective method to improve the aging properties. Aging effect is discussed using space charge distribution and interface energy levels. Abstract: Bi-modified (Zn0.4 Ni0.6 )1- x Na x O (denoted as xZ NN, x < 0.1) ceramics were prepared by conventional solid-state reaction process. The x ZNN ceramics have rock-salt type structure. Besides the rock-salt phase, there is a monoclinic Bi2 O3 secondary phase coexisting in the Bi-modified x ZNN ceramics. These ceramics exhibit typical characteristic of negative temperature coefficient (NTC) of resistivity. The NTC material constants ( B values) of all prepared ceramics are higher than 4000 K. The room temperature resistivity and B values can be adjusted in a large range by altering either or both content of Na-ions and Bi-ions. The effect of Bi2 O3 addition is remarkable in term of enhancing sinter ability to reduce sintering temperature from 1350 °C to 1150 °C, and improving aging stability to drop resistance drift rate from 237 % to 1.8 %. Aging characteristic was discussed based on models of space charge distribution and interfacial barriers.